The Role of Islamic Financial Institutions in the Real Sector: Study of BPRS Bahari Berkesan Financing in Fisheries Agriculture UMKM - Abas, Sofyan (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
In Indonesia, the Micro, Small and Medium Enterprises (UMKM) sector is a pillar of the community's economic support that needs special attention including Islamic banking financial institutions, because the contribution of the UMKM sector to the regional and national economy is quite significant. Sharia People's Financing Bank (BPRS) Bahari Berkesan Kota Ternate has carried out the message of law number 21 of 2008 concerning Islamic banking in Indonesia, namely providing financing based on contracts that do not conflict with sharia principles, namely profit sharing that does not harm both parties, both customers including business actors in the real sector based on MSMEs. Islamic People's Financing Bank (BPRS) Bahari Berkesan Kota Ternate as a financial institution that has the function and role of Financial intermediation is expected to encourage the economic activities of the community, the pattern of fund flow from unproductive parties to productive economic business actors in managing Islamic banking funds including MSME sector actors. This research is qualitative, to find out the extent of the alignment of Islamic financial institutions, especially Islamic banks in the real economic sector including the Micro, Small and Medium Enterprises (UMKM) cluster. Furthermore, the result of this journal research is to be able to find out the pattern of Islamic banking financing, analysis of financing from the Islamic People's Financing Bank (BPRS) Bahari Berkesan Kota Ternate to regional economic business actors in the MSME sector, especially the real sector of agriculture and fisheries.